mRNA Vaccines Against SARS‐CoV‐2 Variants Delivered by Lipid Nanoparticles Based on Novel Ionizable Lipids - Chen, Kepan; Fan, Na; Huang, Hai; Jiang, Xin; Qin, Shugang; Xiao, Wen; Zheng, Qian; Zhang, Yupei; Duan, Xing; Qin, Zeyi; Liu, Yongmei; Zeng, Jun; et al. (Advanced functional materials, 2022)
SARS‐CoV‐2 variants are now still challenging all the approved vaccines, including mRNA vaccines. There is an urgent need to develop new generation mRNA vaccines with more powerful efficacy and better safety against SARS‐CoV‐2 variants. In this study, a new set of ionizable lipids named 4N4T are constructed and applied to form novel lipid nanoparticles called 4N4T‐LNPs. Leading 4N4T‐LNPs exhibit much higher mRNA translation efficiency than the approved SM‐102‐LNPs. To test the effectiveness of the novel delivery system, the DS mRNA encoding the full‐length S protein of the SARS‐CoV‐2 variant is synthesized and loaded in 4N4T‐LNPs. The obtained 4N4T‐DS mRNA vaccines successfully trigger robust and durable humoral immune responses against SARS‐CoV‐2 and its variants including Delta and Omicron. Importantly, the novel vaccines have higher RBD‐specific IgG titers and neutralizing antibody titers than SM‐102‐based DS mRNA vaccine. Besides, for the first time, the types of mRNA vaccine‐induced neutralizing antibodies are found to be influenced by the chemical structure of ionizable lipids. 4N4T‐DS mRNA vaccines also induce strong Th1‐skewed T cell responses and have good safety. This work provides a novel vehicle for mRNA delivery that is more effective than the approved LNPs and shows its application in vaccines against SARS‐CoV‐2 variants. In this study, mRNA vaccines against SARS‐CoV‐2 variants delivered by lipid nanoparticles based on 4N4T lipids are constructed, and successfully trigger robust and durable humoral immune responses against SARS‐CoV‐2 and its variants including Delta and Omicron. In addition, head‐to‐head comparison studies find that the novel 4N4T lipids have a higher mRNA delivery efficiency than SM‐102.